2009
DOI: 10.1038/emboj.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Termination of NF-κB activity through a gammaherpesvirus protein that assembles an EC5S ubiquitin-ligase

Abstract: Host colonisation by lymphotropic gammaherpesviruses depends critically on the expansion of viral genomes in germinal centre (GC) B cells. Yet, host and virus molecular mechanisms involved in driving such proliferation remain largely unknown. Here, we show that the ORF73 protein encoded by the murid herpesvirus-4 (MuHV-4) inhibits host nuclear factor-kappa B (NF-jB) transcriptional activity through poly-ubiquitination and subsequent proteasomal-dependent nuclear degradation of the NF-jB family member p65/RelA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
69
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 42 publications
2
69
0
1
Order By: Relevance
“…In addition to their essential plasmid maintenance activities, these proteins modulate numerous viral and cellular pathways (reviewed in references 37 and 61). For example, KSHV LANA binds to viral DNA and blocks the expression of Rta, the key transcriptional activator of reactivation from latency (32), induces its own expression (45), and modulates the transcription of multiple cellular genes (47). Both KSHV LANA (21) and MHV68 mLANA (19) dysregulate the activity of the tumor suppressor p53, perhaps in part as a means to promote virus growth and prevent cell death (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their essential plasmid maintenance activities, these proteins modulate numerous viral and cellular pathways (reviewed in references 37 and 61). For example, KSHV LANA binds to viral DNA and blocks the expression of Rta, the key transcriptional activator of reactivation from latency (32), induces its own expression (45), and modulates the transcription of multiple cellular genes (47). Both KSHV LANA (21) and MHV68 mLANA (19) dysregulate the activity of the tumor suppressor p53, perhaps in part as a means to promote virus growth and prevent cell death (19).…”
mentioning
confidence: 99%
“…Both KSHV LANA (21) and MHV68 mLANA (19) dysregulate the activity of the tumor suppressor p53, perhaps in part as a means to promote virus growth and prevent cell death (19). Additionally, recent reports have demonstrated the mLANA-mediated proteosomal degradation of the NF-B family member p65/RelA (47) and the activation of G 1 /S cyclin promoters via interaction with cellular bromodomain-containing BET proteins (42).…”
mentioning
confidence: 99%
“…The genetic deletion of the SOCS-box of ORF73 suppresses MuHV-4 expansion in germinal center B cells and prevents persistent MuHV-4 infection in mice. 17 This study suggests that the virus escapes host immune surveillance by using the ubiquitin-dependent proteasomal degradation pathway. In addition to degrading NFkB/p65 via the EC 2/5 S ubiquitin ligase complex, PDLIM2 alone can act as a ubiquitin ligase to induce the ubiquitination and degradation of nuclear p65 in T cells and macrophages.…”
mentioning
confidence: 90%
“…The lymphotropic gammaherpesvirus MuHV-4 (murid herpesvirus-4) ORF73 protein inhibits host NFkB transcriptional activity by inducing NFkB/p65 ubiquitination and degradation. 17 The SOCS-box motif of ORF73 acts by forming one component of the EC 5 S (ElonginC/Cullin5/SOCS) ubiquitin ligase complex. The genetic deletion of the SOCS-box of ORF73 suppresses MuHV-4 expansion in germinal center B cells and prevents persistent MuHV-4 infection in mice.…”
mentioning
confidence: 99%
“…Examples are latency-associated nuclear antigen (LANA) of Kaposi's sarcoma-associated herpesvirus (KSHV) (5,6) and murid herpesvirus 4 (MuHV-4) (7,8) (mLANA and kLANA, respectively), BZLF1 of Epstein-Barr virus (EBV) (9), Vif of human immunodeficiency virus type 1 (HIV-1) (10)(11)(12), and E4orf6/E1B55K of adenovirus (13). Several studies have shown that these viral proteins target multiple cellular substrates for polyubiquitination.…”
mentioning
confidence: 99%